Design language in packaging. - Wijaya, Merwyn. (2012)
Packaging in the beverage industry plays a unique role due to the liquid nature of the product. It does not merely serve as a container, but also gives form to its content, consequently conveying the image and conceptualizing the qualities of the product. Craid is a fictitious brand of Irish beer that is designed based on this essential role. Its name is derived from the word 'cairdeas', which means friendship in Irish. It proposes a new ritual that takes inspiration from the act of breaking bread to share with others, celebrating the bond that they have.